EXPLORING STUDENTS’ STRATEGIES OF VOCABULARY LEARNING AT ENGLISH LANGUAGE EDUCATION STUDY PROGRAM OF KHAIRUN UNIVERSITY - Muhammad Idwar Taha; Ade Ismail; Anwar Ismail (Cakrawala Bahasa, 2023)
This research aims to investigate the use of vocabulary learning strategies used by Economic students. This study was survey study and used mixed method to analyze the data. The techniques of data collection of this study were questionnaire to collect the quantitative data and interview to collect the qualitative data. This research data were collected by using Schmitt’s Vocabulary Learning Strategies (VLS). The data analysis shows that the most frequently strategies used by the students were determination strategies especially in by looking up a word in English-Indonesian dictionary while the least frequently strategies used were social strategies through talking with a native English speaker.